Seismic performance of the superstructure-integrated underground structure based on the integrated simplified seismic analysis method - Dapeng Qiu; Yayue Wang; Tianzi Wang; Yunjuan Chen; Dongye Lin (Soil Dynamics and Earthquake Engineering, 2026)

Quercetin attenuates cisplatin-induced muscle atrophy via Hippo/YAP1 signaling pathway - Jingchun Lv; Jianwei Lin; Xiaojing Chen; Qi Wu; Zhiyao Cao; Dapeng Jiang (Journal of Natural Medicines, 2026)

Pre- and Syn-Mineralization Fracture Patterns in the Sanshandao and Jiaojia Fault Zones and Their Controls on the Distribution of Gold Orebodies: Insights from Numerical Simulations - Chuan Xu; Lin Yang; Qingfei Wang; Shiyu Zhao; Huajian Li; Zhengjiang Ding; Dapeng Li; Zhao Liu (Natural Resources Research, 2026)

Origin, evolution and precipitation mechanism of ore-forming fluids in Jiaojia belt, Jiaodong Peninsula: Insights from trace elements and S Fe isotopes of pyrite - Jinyu Cheng; Lin Yang; Qingfei Wang; Yixin Li; Wen Zhang; Bin Sun; Xue Dong; Shiyu Zhao; Dapeng Li; Kexin Zhao; Hong Wang (Journal of Geochemical Exploration, 2026)

Efficient roxarsone degradation via in-situ H2O2 generation through 2e−ORR over a Pd-Fe2O3 catalyst system - Ruibin Yang; Shuang Yao; Yijun Chen; Zhiwen Jiang; Hangyu Zhang; Ke Wang; Dapeng Li; Feng Liu; Feiyue Qian; Hailiang Yang; Sanjian Ma; Zixia Lin; et al. (Journal of Environmental Management, 2026)

Integrated Analysis of mRNA-seq and miRNA-seq Reveal the Dynamics of the Gonadal Differentiation of Procypris Mera - Zhenling Ke; Weijun Wu; Zhe Li; Yusen Li; Yaoquan Han; Jun Shi; Lilong Chen; Kangqi Zhou; Dapeng Wang; Yong Lin; Min Li; Hua Ye (Marine Biotechnology, 2026)

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

A novel method for pattern recognition of fishing vessel behavior using VMS data - Dapeng Jiang; Guoyou Shi; Lin Ma; Weifeng Li; Qingwu Wang; Guibing Zhu; Xinjian Wang (Ocean Engineering, 2026)

A novel Lu(III)-based rare-earth metal-organic frameworks for rapid detection of phosphate with triple-signal output - Xianfeng Wang; Genchang Chen; Yuanhang Yu; Liyuan Meng; Fengwu Lin; Wenyin He; Jia Chen; Dapeng Zhou; Fangyong Zhu (Food Chemistry, 2026)

N, S, P co-doped carbon dots with yellow emission for high-sensitivity detection and bioimaging of α-lipomycin in salt-sensitive hypertension - Xianfeng Wang; Liyuan Meng; Dapeng Zhou; Bingqing Zhao; Yuanhang Yu; Fengwu Lin; Mingzhu Gao; Gongle Shen; Yang Luo (Chemical Engineering Journal, 2026)

Seismic damage evolution processes of the superstructure-integrated underground structure considering different seismic characteristics - Dapeng Qiu; Dengpan Liu; Yunjuan Chen; Peisen Wang; Dongye Lin (Soil Dynamics and Earthquake Engineering, 2025)

Eukaryotic expression and characterization of two α1,2-fucosyltransferase genes in the histo-blood group antigens synthesis pathway of the Pacific oyster (Crassostrea gigas) - Junxia Hu; Meng Qu; Weiran Zhang; Binbin Gui; Yanhua Jiang; Lin Yao; Shixin Wang; Dapeng Wang (Glycoconjugate Journal, 2025)

Low-carbon investment volatility under policy uncertainty: Evidence from equity markets and implications for carbon capture deployment - Dapeng Lin; Yanfen Wang; Chang Wang; Wen Jiang; Liyuan Zhang; Shuo Hu; Kai Du; Chengdong Yuan (Journal of Cleaner Production, 2025)

PDHA1-mediated H3K18 lactylation is involved in arsenic-induced nonalcoholic fatty liver disease by activating the CD36–NLRP3 inflammasome axis - Han Li; Zhenyang Li; Lin Chen; Xiaoshan Peng; Dapeng Wang; Qian Sun; Yuting Chen; Aihua Zhang; Qizhan Liu; Huanwen Tang (Journal of Hazardous Materials, 2025)

Red mud-based magnetic biochar composite as a peroxydisulfate activator for tetracycline degradation - Chao Shen; Xinxin Dong; Jing Yang; Yafei Li; Shihai Cui; Dapeng Zhang; Xiaochen Lin (Environmental Research, 2025)

Antarctic circumpolar current evolution and its relation to southern hemisphere westerly winds during the holocene - Lingfeng Wan; Dapeng Li; Chenyu Zhu; Zhengyu Liu; Shaoqing Zhang; Xiaopei Lin; Jiuyou Lu (Climate Dynamics, 2025)

Cardamomin Inhibits the Proliferation and Tumorigenesis of Bladder Cancer by ESR1 in PI3K/AKT Pathway - Peng Zhang; Dapeng Song; Zhidong Fang; Dekang Sun; Lin Wang; Lei Shi; Liang Gao; Xudong Jiang (Biochemical Genetics, 2025)

Rapid and in-situ detection of iodine and potassium ferrocyanide in table salt using enhanced-Multipass cavity Raman scattering - Baokun Huang; Chuqiu Zhao; Dapeng Yang; Lin Zhu; Yunhong Zhang; Qishen Huang (Analytica Chimica Acta, 2025)

Progressive-composition-transformation-induced enhanced hyperthermia-based nanozyme towards long-lasting and complete therapy of cancer - Wenlong Zhang; Di Sun; Bin Yang; Jiaqi Liu; Yilin Yuan; Dezhuang Li; Yuliang Sun; Guoqiang Guan; Yanli Liu; Dapeng Wu; Hong Liao; Juntang Lin; et al. (Chemical Engineering Journal, 2025)

Heterogeneous Fenton-like catalysts of tetranitro iron phthalocyanine@Fe3O4@fly ash composites for fast decomposition of environmental contaminants - Dapeng Li; Peng Zhang; Yang Jin; Qing Li; Xinyuan Li; Ruirui Chang; Ruoxi Ma; Lin Yan; Suxiang Ge; Juntao Ma (Waste Disposal & Sustainable Energy, 2025)
Using fly ash (FA) solid wastes as economical carriers to construct Fenton-like catalytic composites with additional functions is more practical than the use of a single catalyst. Understanding the structure and properties of catalysts and carriers is vital to improve performance. Tetranitro iron phthalocyanine (TNFePc) is a highly active molecular catalyst, whose immobilization and Fenton-like heterogeneous catalysis remain unclear. In this study, magnetically recyclable composites of TNFePc@Fe 3 O 4 @FA were successfully fabricated. Further, Fe 3 O 4 nanocrystals decorated on FA surfaces could be used as special functional layer for composite recycling and simultaneous in situ TNFePc synthesis. Peroxides of H 2 O 2 , KHSO 5 , and tert-butyl hydrogen could be effectively activated by composites and transformed into highly reactive radicals. Moreover, molecular oxygen could be activated as well. Model pollutants, methylene blue and oxytetracycline, could be synergistically degraded by the radical oxidation of superoxide, hydroxyl, alkoxy, and sulfate radicals and non-radical oxidation of high-valent iron-oxo species of TNPcFe IV =O. To the best of our knowledge, this is the first design of FA-based composites with dual function, Fenton-like heterogeneous catalysis and magnetic recyclability, for environmental decontamination. Graphical abstract

A Dynamic Trajectory Temporal Density Model for Analyzing Maritime Traffic Patterns - Dapeng Jiang; Guoyou Shi; Lin Ma; Weifeng Li; Xinjian Wang; Guibing Zhu (Journal of Marine Science and Engineering, 2025)
This study investigates the spatiotemporal density aggregation and pattern distribution of vessel traffic amidst bustling maritime logistics scenarios. Firstly, a relatively new spatiotemporal segmentation and reconstruction method is proposed for ship AIS trajectories to address trajectory disruptions caused by berthing, anchorage, and other factors. Subsequently, a trajectory filtering algorithm utilizing time window panning is introduced to mitigate position jumps and deviation errors in trajectory points, ensuring that the dynamic trajectory adheres to the spatiotemporal correlations of ship motion. Secondly, to establish a geographical spatial mapping of dynamic trajectories, spatial gridding is applied to maritime traffic areas. By associating the geographical space of traffic activities with the temporal attributes of dynamic trajectories, a dynamic trajectory temporal density model is constructed. Finally, a case study is conducted to evaluate the effectiveness and applicability of the proposed method in identifying spatiotemporal patterns of maritime traffic and spatiotemporal density aggregation states. The results show that the proposed method can identify dynamic trajectory traffic patterns after the application of compression algorithms, providing a novel approach to studying the spatiotemporal aggregation of maritime traffic in the era of big data.

Self-powered photoelectrochemical sensor based on molecularly imprinted polymer-coupled CBFO photocathode and Ag2S/SnS2 photoanode for ultrasensitive dimethoate sensing - Shuqin Chen; Wanfu Lan; Dapeng Yang; Jingying Xu; Yikun Hu; Hetong Lin; Liang Feng (Analytica Chimica Acta, 2025)

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

High-intensity ultrasound-modified Jerusalem artichoke leaf protein for stabilizing corn oi-in-water emulsion and Enhacing curcumin delivery - Dongjie Huang; Rili Hao; Wenyuan Zhang; Yiyan Liu; Xinru Lin; Weixuan Song; Yang Jiang; Dongxiao Sun-Waterhouse; Dapeng Li (Food Chemistry, 2025)

Driving factors of molybdenum (Mo) bioconcentration in maize in the Longitudinal Range–Gorge Region of Southwestern China - Zhiliang Wu; Qingye Hou; Zhongfang Yang; Tao Yu; Dapeng Li; Kun Lin; Xuezhen Li; Bo Li; Changchen Huang; Jiaxin Wang (Environmental Geochemistry and Health, 2024)

Regional disparities and technological approaches in heavy metal remediation: A comprehensive analysis of soil contamination in Asia - Lu Liu; Jialin Wang; Jieru Zhai; Dapeng Yan; Zhengda Lin (Chemosphere, 2024)

Investigation of Crack Propagation and Failure of Liquid-Filled Cylindrical Shells Damaged in High-Pressure Environments - Hongshuo Zhang; Dapeng Tan; Shicheng Xu; Tiancheng Hu; Huan Qi; Lin Li (Journal of Marine Science and Engineering, 2024)
Cylindrical shell structures have excellent structural properties and load-bearing capacities in fields such as aerospace, marine engineering, and nuclear power. However, under high-pressure conditions, cylindrical shells are prone to cracking due to impact, corrosion, and fatigue, leading to a reduction in structural strength or failure. This paper proposes a static modeling method for damaged liquid-filled cylindrical shells based on the extended finite element method (XFEM). It investigated the impact of different initial crack angles on the crack propagation path and failure process of liquid-filled cylindrical shells, overcoming the difficulties of accurately simulating stress concentration at crack tips and discontinuities in the propagation path encountered in traditional finite element methods. Additionally, based on fluid-structure interaction theory, a dynamic model for damaged liquid-filled cylindrical shells was established, analyzing the changes in pressure and flow state of the fluid during crack propagation. Experimental results showed that although the initial crack angle had a slight effect on the crack propagation path, the crack ultimately extended along both sides of the main axis of the cylindrical shell. When the initial crack angle was 0°, the crack propagation path was more likely to form a through-crack, with the highest penetration rate, whereas when the initial crack angle was 75°, the crack propagation speed was slower. After fluid entered the cylindrical shell, it spurted along the crack propagation path, forming a wave crest at the initial ejection position.

A Direction-Preserved Vessel Trajectory Compression Algorithm Based on Open Window - Lin Ma; Guoyou Shi; Weifeng Li; Dapeng Jiang (Journal of Marine Science and Engineering, 2023)
Ship trajectory data can be used in most marine-related research, and most ship trajectory data come from AIS. The large number of ships and the short reporting period of AIS have resulted in a huge amount of ship trajectory data, which has caused a certain amount of pressure on the relevant research. This paper proposes a direction-preserved vessel trajectory compression method based on Open Window, which can effectively retain the direction change feature points while ensuring the position error. In addition, the method can work in both offline and online modes. Also, the velocity threshold and low-speed redundancy points problems are considered. In order to verify the effect of the proposed method and the adaptability of the method to different feature data, a parallel experiment was performed on port water and coastal water datasets. The results show that our method can compress vessel trajectories while retaining the feature points. Meanwhile, by comparing it with the compression method that is based on distance thresholds, the vessel trajectory compress time is drastically reduced by up to 87.3% in the port water data. The research in this paper provides a new method through which to compress vessel trajectories for research in marine-related fields on vessel trajectory.

Combined effects of microcystin-LR and rice straw-derived biochar on the hepatic antioxidant capacity of zebrafish: Insights from LC-MS/MS-based metabolomics analysis - Wang Lin; Kang Ouyang; Ya He; Hui Yang; Yu Kuang; Dapeng Li; Li Li (Science of The Total Environment, 2023)

The 4 January 2020 offshore Pearl River Estuary earthquake sequence in South China: Implications for seismic potential of the NW-striking local faults - Shaohong Xia; Jiangnan Lin; Dapeng Zhao; Jinghe Cao; Changrong Zhang; Xinyang Wang; Kuiyuan Wan; Chaoyan Fan (Journal of Asian Earth Sciences, 2023)

Hsa_circ_0001535 Regulates Colorectal Cancer Progression via the miR-433-3p/RBPJ Axis - Zihan Mao; Dapeng Lin; Jian Xu (Biochemical Genetics, 2023)

TRFM-LS: Transformer-Based Deep Learning Method for Vessel Trajectory Prediction - Dapeng Jiang; Guoyou Shi; Na Li; Lin Ma; Weifeng Li; Jiahui Shi (Journal of Marine Science and Engineering, 2023)
In the context of the rapid development of deep learning theory, predicting future motion states based on time series sequence data of ship trajectories can significantly improve the safety of the traffic environment. Considering the spatiotemporal correlation of AIS data, a trajectory time window panning and smoothing filtering method is proposed for the abnormal values existing in the trajectory data. The application of this method can effectively deal with the jump values and outliers in the trajectory data, make the trajectory smooth and continuous, and ensure the temporal order and integrity of the trajectory data. In this paper, for the features of spatiotemporal data of trajectories, the LSTM structure is integrated on the basis of the deep learning Transformer algorithm framework, abbreviated as TRFM-LS. The LSTM module can learn the temporal features of spatiotemporal data in the process of computing the target sequence, while the self-attention mechanism in Transformer can solve the drawback of applying LSTM to capture the sequence information weakly at a distance. The advantage of complementarity of the fusion model in the training process of trajectory sequences with respect to the long-range dependence of temporal and spatial features is realized. Finally, in the comparative analysis section of the error metrics, by comparing with current state-of-the-art methods, the algorithm in this paper is shown to have higher accuracy in predicting time series trajectory data. The research in this paper provides an early warning information reference for autonomous navigation and autonomous collision avoidance of ships in practice.

Genome-wide association study reveals markers and candidate genes associated with growth in the rice flower carp, an economic fish species of integrated rice-fish culture in China - Hui Luo; Xianhui Pan; Yin Huang; Zhe Li; Hua Ye; Kangqi Zhou; Luting Wen; Junqi Qin; Wenping He; Xuesong Du; Dapeng Wang; Yong Lin (Frontiers in Marine Science, 2023)
The rice flower carp ( Cyprinus carpio ) is an important fish in integrated rice-fishery farming. Here, we performed the first genome-wide association study (GWAS) for seven growth traits (including body mass, total length, body length, body height, body width, caudal-peduncle depth, and eye spacing) in 200 rice flower carp samples using 369,688 high-quality SNPs and 42,225 indels obtained by double-digest genotyping-by-sequencing (ddGBS). The morphometrics of these traits were highly correlated (Pearson’s correlation coefficients = 0.74–0.99, p < 0.001). GWAS detected 15, 5, 4, 26, 7, 16, and 17 loci significant associated (-log10P ≥ 5) with body mass, total length, body length, body width, body height, caudal-peduncle depth, and eye spacing, respectively. Subsequently, within the 50 kb upstream and downstream regions surrounding these significant loci, 38, 19, 18, 20, 52, 27, and 37 candidate genes for the seven growth traits were detected, respectively. Importantly, B6_4352672 and A8_4978825 were significantly associated with more than five growth traits. These results showed loci significantly associated with more than five growth traits will be helpful for future marker-assisted selection (MAS). Interestingly, chromosomes A8 and B25 had many loci significantly associated with growth traits, most of which were shared among multiple growth-related traits. These results indicated that chromosome A8 and B25 may be closely related to growth traits. Our findings not only help understand the genetic architecture of growth traits in fish but facilitate the identification of candidate genes for marker-assisted selection towards breeding faster-growing rice flower carp in the future.

Mining the synergistic effect in hydrothermal co-liquefaction of real feedstocks through machine learning approaches - Jie Yu; Xiaomei Zhong; Zhilin Huang; Xiaoyu Lin; Haiyong Weng; Dapeng Ye; Quan (Sophia) He; Jie Yang (Fuel, 2023)

Top‐down controls on nutrient cycling and population dynamics in a model estuarine photoautotroph–heterotroph co‐culture system - Qiang Zheng; Wenxin Lin; Yu Wang; Dapeng Xu; Yanting Liu; Nianzhi Jiao (Molecular Ecology, 2021)
Viral lysis and protistan grazing are thought to be the major processes leading to microbial mortality in aquatic environments and thus regulate community diversity and biogeochemical cycling characteristics. Here, we studied nutrient cycling and bacterial responses to cyanophage‐mediated photoautotroph lysis and ciliate predation in a model Synechococcus –heterotroph co‐culture system. Both viral lysis and Euplotes grazing facilitated the transformation of organic carbon from biomass to dissolved organic matter with convention efficiencies of 20%–26%. The accumulation of ammonium after the addition of phages and ciliates suggested the importance of recycled NH 4 + occurred in the interactions between Synechococcus growth and heterotrophic bacterial metabolism of photosynthate. The slower efficiency of P mineralization compared to N (primarily ammonium) indicated that P‐containing organic matter was primarily integrated into bacterial biomass rather than being remineralized into inorganic phosphate under C‐rich conditions. In the cyanophage addition treatment, both Fluviicola and Alteromonas exhibited rapid positive responses to Synechococcus lysing, while Marivita exhibited an apparent negative response. Further, the addition of Euplotes altered the incubation system from a Synechococcus ‐driven phycosphere to a ciliate‐remodelled zoosphere that primarily constituted grazing‐resistant bacteria and Euplotes symbionts. Top‐down controls increased co‐culture system diversity and resulted in a preference for free‐living lifestyles of dominant populations, which was accompanied by the transfer of matter and energy. Our results indicate top‐down control was particularly important for organic matter redistribution and inorganic nutrient regeneration between photoautotrophs and heterotrophs, and altered bacterial lifestyles. This study consequently sheds light on marine biogeochemical cycling and the interaction networks within these dynamic ecosystems.

NOD1 inhibits proliferation and enhances response to chemotherapy via suppressing SRC-MAPK pathway in hepatocellular carcinoma - Xiaomin Ma; Yumin Qiu; Lihui Zhu; Yunxue Zhao; Yueke Lin; Dapeng Ma; Zhenzhi Qin; Caiyu Sun; Xuecheng Shen; Tao Li; Lihui Han (Journal of Molecular Medicine, 2020)

The genetic relationship between Habo alkaline intrusion and its surrounding deposits, Yunnan Province, China: geological and S–Pb isotopic evidences - Zhongneng Meng; Qian Zhang; Lin Ye; Yupin Liu; Jiangbo Lan; Dapeng Wang (Acta Geochimica, 2016)

Developing Single Nucleotide Polymorphism (SNP) Markers for the Identification of Coffee Germplasm - Lin Zhou; Fernando E. Vega; Huawei Tan; Aixa E. Ramírez Lluch; Lyndel W. Meinhardt; Wanping Fang; Sue Mischke; Brian Irish; Dapeng Zhang (Tropical Plant Biology, 2016)

Combined effect of ligament stem cells and umbilical-cord-blood-derived CD34+ cells on ligament healing - Dapeng Jiang; Shulong Yang; Peng Gao; Yubo Zhang; Tieyun Guo; Houwei Lin; Hongquan Geng (Cell and Tissue Research, 2015)

Effects of ginsenoside Re on rat jejunal contractility - Yongjian Xiong; Dapeng Chen; Bochao Lv; Fangfei Liu; Qiying Yao; Zeyao Tang; Yuan Lin (Journal of Natural Medicines, 2014)

Studies on Correlation Between Single-Nucleotide Polymorphisms of Tumor Necrosis Factor Gene and Different Stages of Ankylosing Spondylitis - Yinghua Ji; Xiaoyu Yang; Lin Yang; Dapeng Wu; Fangfang Hua; Tan Lu; Jinling Jia; Chao Ma; Qiudong Liang (Cell Biochemistry and Biophysics, 2013)